Pattern of Anterior Cruciate Ligament Reconstruction (ACLR) among Athletes in Malaysia between 2015 and 2020 - Fariza Zainudin Fairus; Siti Aisyah Ibrahim; Ali Md Nadzalan; Badrul Akmal Hisham Md Yusoff; Norlelawati Mohamad; Efri Noor Muhammad Hendri; Deepashini Harithasan; Ruaibah Yazani Tengah; Nor Azlin Mohd Nordin (Physical Education Theory and Methodology, 2022)
Background. Individual involvement in sports activity is rising and thus increases the risk of knee injury. Anterior Cruciate Ligament (ACL) rupture is the most common knee injury requiring ACL reconstruction (ACLR). However, limited evidence is available to date on ACLR characteristics in Malaysia for comparison with Western countries. This study aims to describe the epidemiological characteristic of ACLR surgery and the trend of pre-operative physiotherapy (pre-habilitation).